Developing HLA distributed simulations using Model-Driven DSEEP with OPM - Schittler, João Gabriel da Cunha; Brites, Alexandre Chagas; Gressler, Henrique de Oliveira; Nunes, Raul Ceretta (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames); 2024: Anais do XXIII Simpósio Brasileiro de Jogos e Entretenimento DigitalDO - 10.5753/sbgames.2024.241231, 2024)
Distributed simulations aim to replicate real-world behavior viacomputer networks. Developing source code for such simulations, especiallywhile following standards like High-Level Architecture (HLA), is often error-prone due to its complexity, prompting code generators requiring abstractmodels. This work proposes a model-driven methodology that explores theObject-Process Methodology (OPM) modeling language in conjunction withUML to generate accurate and readable high-level models in DSEEP andtransform them into code. For results, we present a case study in which astakeholder with no prior knowledge of OPM was tasked and succeeded withmodeling a distributed simulation to show how learnable and understandableOPM is, bridging the gap between conceptualization and implementation.